Method of Lecture and Discussion: Increasing Islamic Understanding - Erma Nurdaningsih; Imam Tabroni; Dinda Putri; Wishal Luthfikha (PT FORMOSA CENDEKIA GLOBAL, 2023)
The law of shari'a is an obligation that must be applied by all muslims especially mukallaf. Shari'a has 2 types, namely taklifi and wadh'i. The purpose of this study is to find out how to understand Syara's law by using the lecture and discussion method at the KRS Cisereuh Taklim Assembly, in addition to how to improve the understanding of Syara law using the lecture and discussion method at the KRS Cisereuh Taklim Assembly. The theoretical foundations used in this study are the experts of ushul fiqih, Hasan Langgunlung and Muhammad Abdul Rahim. The research method in this article uses a descriptive qualitative method with an interview approach. The results of the study on this artilcle were from 25 people who took part in the monthly study at the KRS Cisereuh Taklim Assembly using the lecture and discussion method, there was an increase in understanding by 19 people and there was no increase of only 6 people